Sociodemographic factors associated with fruit and vegetable consumption among adolescents in urban Saudi Arabia - Israa M Shatwan (International Journal of Food and Nutritional Health, 2026)
Healthy eating practices and higher consumption of fruits and vegetables during childhood and adolescence are known to reduce the future risk of developing several health problems. This cross-sectional study investigated the association between sociodemographic factors and fruit and vegetable consumption scores among 104 adolescents aged 13–18 years in Jeddah, Saudi Arabia. Sociodemographic factors included age, gender, school type (private or public), body mass index of the adolescents and their parents, parents’ education level (high school or below, bachelor’s degree, or postgraduate), parents’ occupation (employed or unemployed), number of family members, and family income. Daily intake of fruits and vegetables was assessed using a short food frequency questionnaire, which included 18 and 22 questions on the frequency of consumption of different fruits and vegetables, respectively. Adolescents attending public school (p = 0.02) and those with large family size (p = 0.006) had significantly higher fruit intake score. Father’s obesity status tended to be positively related to vegetable consumption score. These significant factors were more observed among adolescents with normal body mass index (p < 0.05). Additionally, higher family income was significantly associated with higher vegetable consumption scores (p =0.02) only among adolescents with normal body mass index. Adolescents whose fathers had obesity consumed more vegetables (1.58±0.94) than those whose fathers’ body mass index was normal (1.16±0.81). Family was the main contributor to the quantity of fruits and vegetables consumed among urban Saudi adolescents.